2022
DOI: 10.1038/s41419-022-05501-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell-specific molecule 1 drives cervical cancer progression

Abstract: The expression, biological functions and underlying molecular mechanisms of endothelial cell-specific molecule 1 (ESM1) in human cervical cancer remain unclear. Bioinformatics analysis revealed that ESM1 expression was significantly elevated in human cervical cancer tissues, correlating with patients’ poor prognosis. Moreover, ESM1 mRNA and protein upregulation was detected in local cervical cancer tissues and various cervical cancer cells. In established and primary cervical cancer cells, ESM1 shRNA or CRISPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The study notably signifies the first in-depth exploration of ESM1’s role in PTC, emphasizing its overexpression and critical involvement in cell proliferation and migration. Following ESM1 inhibition via shRNA, we observed decreased cellular growth and increased apoptosis rates, supporting ESM1’s value as a therapeutic target [ 21 24 ]. The profound impact of ESM1 knockdown on cellular mechanisms not only bolsters its position as a viable prognostic biomarker but also as a potential therapeutic agent in thyroid cancer.…”
Section: Discussionmentioning
confidence: 67%
“…The study notably signifies the first in-depth exploration of ESM1’s role in PTC, emphasizing its overexpression and critical involvement in cell proliferation and migration. Following ESM1 inhibition via shRNA, we observed decreased cellular growth and increased apoptosis rates, supporting ESM1’s value as a therapeutic target [ 21 24 ]. The profound impact of ESM1 knockdown on cellular mechanisms not only bolsters its position as a viable prognostic biomarker but also as a potential therapeutic agent in thyroid cancer.…”
Section: Discussionmentioning
confidence: 67%
“…Recent studies have revealed that ESM1 is highly expressed in a variety of malignancies, including lung, kidney, liver, breast, and brain glioblastoma and that it is associated with tumor angiogenesis, metastasis, and poor prognosis (22)(23). However, to the best of our knowledge, its role on the proliferation and migration of thyroid cancer cells has not been previously explored.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Li YK et al showed that ESM1 overexpression facilitated cell proliferation, migration, and angiogenesis in ovarian cancer cells via the Akt pathway 38 . Furthermore, Lu JJ et al revealed that ESM1 augmented the PI3K signaling pathway and accelerated EMT in cervical cancer 39 . Compared to these results, our research harbored the following differences: Firstly, we studied the clinical correlation between ESM1 and CSCC patients based on clinical sample studies and bioinformatics analysis of the TCGA database; The conclusions are consistent with previous studies; Then, through in vitro experiments, a preliminary study was conducted on the expression of ESM1 through VEGFα/VEGFR2/ERK and hypoxia-related signaling pathways regulate tumor microvascular formation; The different molecular mechanism compared to previous studies suggested that ESM1 might participate in the occurrence and development of CSCC through multiple avenues.…”
Section: Discussionmentioning
confidence: 99%